2005
DOI: 10.1007/bf03030531
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal and seasonal patterns of nitrogen fixation in analnus hirsuta plantation of central Korea

Abstract: We used an acetylene reduction assay to measure rates of nitrogen fixation on a 38-year-old Alnus hirsuta plantation in central Korea. The diurnal pattern of acetylene reduction changed significantly during May, August, and October, typically varying by 3-fold throughout the course of the day. Maximum rates occurred at 3 p.m. in May and October, but at 6 p.m. in August. Increasing trends were evident during the early growing season, with sustained high rates from mid-May through late September; July had the hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 19 publications
(20 reference statements)
3
17
1
Order By: Relevance
“…For instance, Shin et al [57] reported notable atmospheric N deposition in Seoul (16.5 kg N·ha for NO3 − , NO2 and HNO3 deposits); the BAF is located within the range of the urban effect on atmospheric N deposition [61]. N fixation of pure alder forests was known to be 37-150 kg N·ha −1 ·year −1 [62]. Even though lack of atmospheric N deposition and N fixation data in our study limits the certainty and depth of this implication, evidences from other studies suggest that there may be sufficient NH4 + sources without N mineralization.…”
Section: Restricted Net N Mineralization Under Nh4 + Rich Conditionmentioning
confidence: 99%
“…For instance, Shin et al [57] reported notable atmospheric N deposition in Seoul (16.5 kg N·ha for NO3 − , NO2 and HNO3 deposits); the BAF is located within the range of the urban effect on atmospheric N deposition [61]. N fixation of pure alder forests was known to be 37-150 kg N·ha −1 ·year −1 [62]. Even though lack of atmospheric N deposition and N fixation data in our study limits the certainty and depth of this implication, evidences from other studies suggest that there may be sufficient NH4 + sources without N mineralization.…”
Section: Restricted Net N Mineralization Under Nh4 + Rich Conditionmentioning
confidence: 99%
“…Nodule biomass varies depending on stand age, species composition, tree size, stand density, and soil nutrient concentrations (Binkley 1981(Binkley , 1982Bormann and Gordon 1984;Sharma and Ambasht 1986;Binkley et al 1992;Uliassi and Ruess 2002;Lee and Son 2005;Son et al 2007) and has been estimated to range from 16 to 480 kg ha -1 (Table 1; Binkley 1981;Hurd et al 2001). No clear association has been found between nodule biomass and stand age but nodule biomass tends to increase early until a stand is 10-15 years old (Fig.…”
Section: Nodule Biomass In Alnus Standsmentioning
confidence: 99%
“…This character of nodules may help Alnus species adapt to photosynthesis under elevated CO 2 conditions (Koike et al 1997;Tobita et al 2010bTobita et al , 2011), as will be described in detail hereinafter. Alnus species N 2 fixation rates are estimated to be several kg N ha -1 year -1 to 320 kg N ha -1 year -1 after several major assumptions are met (Table 2; e.g., Binkley 1981;Hibbs and Cromack 1990;Rytter et al 1991;Cleveland et al 1999;Hurd et al 2001;Lõhmus et al 2002;Uri et al 2004;Lee and Son 2005). The nitrogenase activity of each nodule and N 2 fixation rate per plant vary depending on the N demand with increasing tree age (Son et al 2007).…”
Section: Nodule Biomass In Alnus Standsmentioning
confidence: 99%
“…Respiration appeared to be limited more by temperature and PAR rather than by moisture for all three sites. Nevertheless, more research is necessary about the influence of vegetation on soil respiration on those sites (Mathes and Schriefer, 1985;Weber, 1990;Wagai et al, 1998;Lee and Son, 2005).…”
Section: Soil Respirationmentioning
confidence: 99%